2021
DOI: 10.1080/15361055.2020.1858671
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Thin-Film MHD Flow for Nonuniform Conductivity Walls

Abstract: Liquid metals offer unique properties and their use in a nuclear fusion reactor, both as confined flows and free surface flow, is widely studied in the fusion community. The interaction between this conductive fluid and the tokamak magnetic fields leads to Magnetohydrodynamic (MHD) phenomena that influence the flow features. To properly design components that employ liquid metals, it is necessary to accurately predict these features and, although the efforts made in development, a mature code specifically cust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Figure 13 and Figure 14 show the velocity and temperature distribution at Ha = 9159 In broad agreement with the previous studies [27,28], no temperature fluctuations were identified after 100-300 s of transient, and heat transfer was still dominated by conduction Flow repartition is expected to reach up to 300% of the nominal flow (0.155 kg/s) for the terminal ones and as low as 25% for the equatorial ones. These values must be intended as indicative since they are going to be affected by coupling, even if the accurate agreement in terms of overall pressure loss between our model and CFD calculations for the WCLL TBM (see Ref.…”
Section: This Studysupporting
confidence: 88%
See 1 more Smart Citation
“…Figure 13 and Figure 14 show the velocity and temperature distribution at Ha = 9159 In broad agreement with the previous studies [27,28], no temperature fluctuations were identified after 100-300 s of transient, and heat transfer was still dominated by conduction Flow repartition is expected to reach up to 300% of the nominal flow (0.155 kg/s) for the terminal ones and as low as 25% for the equatorial ones. These values must be intended as indicative since they are going to be affected by coupling, even if the accurate agreement in terms of overall pressure loss between our model and CFD calculations for the WCLL TBM (see Ref.…”
Section: This Studysupporting
confidence: 88%
“…Figure 12 shows the differential pressure between OB BZ cells, which is qualitatively consistent with [26], even if coupling is currently not modeled in R5-MHD. Dedicated CFD analyses have also been conducted to characterize the magnetoconvective regime in the OB equatorial elementary cell considering an idealized pipe layout (straight toroidal tubes) [27]. Compared to previous studies [28,29], the present model aimed to investigate the effect of a skewed magnetic field, more accurate FW thermal boundary conditions and higher magnetic field intensity (≈4 T, Ha = 9159).…”
Section: This Studymentioning
confidence: 99%
“…He used a Galerkin method with two basic functions in the Y-direction, the parabola, and the Hartmann profile, to approximate the velocity profile along the magnetic field lines. Results of Shishko model were confirmed by the fully developed CFD analysis using CFX [52]. In the analytical model we used a drag formula from Shishko paper and applied it at each cross-section for the developing flow on the horizontal plate as shown below:…”
Section: Analytical Modelmentioning
confidence: 89%
“…Overall, interIsoFoam has proven to be able to correctly simulate the basic characteristics of a flow with a high density ratio, therefore it is an excellent candidate for the future implementation of the MHD equations, following the methodology presented by Zhang et al [41], for the study of the migration of helium bubbles in the blanket [2,3], but also in the framework of the advanced PFCs [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of analysing these effects through an MHD solver capable of simulating mixtures of a liquid metal and a gas is, indeed, very important both for the design of the breeding blanket [2,3] and for the plasma-facing components, in which advanced solutions may foresee the employment of liquid metal films, jet curtains and other solutions to protect the solid substrate below from the thermal and radiative load coming from the plasma [17][18][19].…”
Section: Introductionmentioning
confidence: 99%